Estimation of air–water gas exchange coefficient in a shallow lagoon based on 222Rn mass balance. (May 2015) - Cockenpot, S.; Claude, C.; Radakovitch, O.
Abstract: The radon-222 mass balance is now commonly used to quantify water fluxes due to Submarine Groundwater Discharge (SGD) in coastal areas. One of the main loss terms of this mass balance, the radon evasion to the atmosphere, is based on empirical equations. This term is generally estimated using one among the many empirical equations describing the gas transfer velocity as a function of wind speed that have been proposed in the literature. These equations were, however, mainly obtained from areas of deep water and may be less appropriate for shallow areas. Here, we calculate the radon mass balance for a windy shallow coastal lagoon (mean depth of 6 m and surface area of 1.55*10 8 m 2 ) and use these data to estimate the radon loss to the atmosphere and the corresponding gas transfer velocity. We present new equations, adapted to our shallow water body, to express the gas transfer velocity as a function of wind speed at 10 m height (wind range from 2 to 12.5 m/s). When compared with those from the literature, these equations fit particularly well with the one ofKremer et al. (2003) . Finally, we emphasize that some gas transfer exchange may always occur, even for conditions without wind. Highlights: We used, for the first time, a radon mass balance approach to determine gas transfer exchange in a shallow area. We were more particularly able to highlight that gas transfer occurred for low wind or for conditions without winds. We also expressed new expressions for the gas transfer coefficient as a function of wind speed in shallow areas.